Impact of a Multidisciplinary Care Model on Clinical Outcomes and Healthcare Utilization in Patients with Multimorbidity - Lena M. Müller, Tobias K. Schneider, Sophia P. Weber (Academic Journal of Clinicians, 2025)
Background Patients with multimorbidity face complex health challenges that require coordinated care. A multidisciplinary care model may enhance clinical outcomes and reduce healthcare utilization. Objective This study evaluates the impact of a multidisciplinary care model on clinical outcomes and healthcare utilization in patients with multimorbidity. Methods A quasi-experimental study was conducted with 300 patients diagnosed with multimorbidity, divided into two groups: one receiving standard care (n=150) and the other receiving multidisciplinary care (n=150) that included physicians, nurses, social workers, and pharmacists. Clinical outcomes were assessed using health-related quality of life (HRQoL) measures and hospitalization rates over 12 months. Results Patients in the multidisciplinary care group reported significant improvements in HRQoL scores (mean increase of 15 points, p < 0.01) compared to the standard care group. Hospitalization rates decreased by 30% in the multidisciplinary group (p < 0.05). Additionally, there was a notable reduction in emergency department visits (20% decrease, p < 0.05). Conclusions Implementing a multidisciplinary care model significantly improves clinical outcomes and reduces healthcare utilization in patients with multimorbidity. These findings support the integration of multidisciplinary teams in managing complex health needs, highlighting the potential for better patient care and resource efficiency.